The concept of S.M.Voronin in the problem of comparisons of deterministic and random computation in the same terms - Temirgaliyev, Н. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2019)
The paper was devoted to propose of S.M.Voronin to evaluate the quality of deterministic and non-deterministic calculation methods in theoretical and practical aspects through probabilistic measures on functional classes in the same language .